Policy for the Improvement of Education and Training (PIM-4) for Civil Servants in the Department of Education and Culture of North Bolaang Mongondow Regency: Kebijakan Peningkatan Pendidikan Dan Pelatihan (PIM-4) Aparatur Sipil Negara Di Dinas Pendidikan Dan Kebudayaan Kabupaten Bolaang Mongondow Utara - Firda Humokor; Jusrin Kadir; Yahya Antu (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This type of research is descriptive research with a qualitative approach. This study aims to obtain and know an overview of the Education and Training Improvement Policy (PIM-4) for State Civil Apparatus at the Education and Culture Office of North Bolaang Mongondow Regency. The results of this study indicate that the synchronization of employee placement has not run optimally and has not complied with standard operating procedures, there is a problem of lack of coordination from the leadership and the agency in terms of placement, the budget for education and training activities is very lacking, so the participant quota must be reduced because it adjusts the budget available at SKPD, poor coordination carried out by each employee is limited and there is a lack of coordination because in making decisions on placement and training policies it is not in accordance with the scientific field. Suggestions need to be improved regarding data synchronization, budget additions, and coordination so that the Improvement of Education and Training (PIM-4) for State Civil Servants at the Education and Culture Office of North Bolaang Mongondow Regency can run optimally